2017
DOI: 10.5578/fmbd.53781
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Cytotoxicity and Molecular Effects Related to Silicon Nanoparticles Exposures

Abstract: Silicon nanoparticles are widely used for various applications including environmental, biological, chemical and physical. And, to translate these nanomaterials to the clinic and industrial domains, their safety needs to be verified, particularly in terms of genotoxicity and cytotoxicity. Therefore, in this study, we aimed to investigate of cytotoxicity and changes in gene expression profiles influenced by commonly silicon (as silicon carbide, silicon dioxide, silicon nitride) nanoparticles in human alveolar e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
(33 reference statements)
3
0
0
Order By: Relevance
“…One of the interesting results obtained in this investigation is the considerable, concentration-dependent, cytotoxic, and genotoxic effects of both SiNPs treatments. This result is consistent with the finding of Aydin et al (2017) who reported an inducing effect of SiNPs for cytotoxicity in a dose-dependent manner. Moreover, genetic changes due to apoptosis and/or DNA damage or repair were also reported.…”
Section: Discussionsupporting
confidence: 93%
“…One of the interesting results obtained in this investigation is the considerable, concentration-dependent, cytotoxic, and genotoxic effects of both SiNPs treatments. This result is consistent with the finding of Aydin et al (2017) who reported an inducing effect of SiNPs for cytotoxicity in a dose-dependent manner. Moreover, genetic changes due to apoptosis and/or DNA damage or repair were also reported.…”
Section: Discussionsupporting
confidence: 93%
“…One of the interesting results obtained in this investigation is the considerable, concentration-dependent, cytotoxic, and genotoxic effects of both SiNPs treatments. This result is consistent with the finding of Aydin et al (2017) who reported an inducing effect of SiNPs for cytotoxicity in a dose-dependent manner. Moreover, genetic changes due to apoptosis and/or DNA damage or repair were also reported.…”
Section: Discussionsupporting
confidence: 93%
“…One of the interesting results obtained in this investigation is the considerable, concentration-dependent, cytotoxic, and genotoxic effects of both SiNPs treatments. This result is consistent with the finding of Aydin et al (2017) who reported an inducing effect of SiNPs for cytotoxicity in a dose-dependent manner. Moreover, genetic changes due to apoptosis and/or DNA damage or repair were also reported.…”
Section: Discussionsupporting
confidence: 93%